Immune response and protection provided by live tachyzoites and native antigens from the NC-6 Argentina strain of Neospora caninum in pregnant heifers - Hecker, Yanina Paola (2013)
The aim of the present study was to compare the immunogenicity and protective efficacy of live tachyzoites and native antigen extract obtained from the NC-6 Argentina strain against vertical transmission of Neospora caninum, following experimental challenge in pregnant heifers with the NC-1 strain. Sixteen pregnant heifers were divided in 4 groups of 4 animals, each receiving different inoculation before mating: group A animals were intravenously (iv) inoculated with 6.25×107 live tachyzoites of the NC-6 strain, group B heifers were inoculated twice subcutaneously (sc) with N. caninum native antigen extract formulated with ISCOMs, group C heifers were sc injected with sterile phosphate-buffered saline (PBS) and group D heifers received sc ISCOM-matrix (ISCOMs without antigen). All groups were iv challenged with the NC-1 strain at 70 days of gestation. Serum and heparinized blood samples were collected eight times on weeks 0, 2, 3, 5, 9, 13, 16 and 17 post-inoculation. Dams were slaughtered at the 17th week of experiment (104 days of pregnancy) and placental and fetal tissue samples were collected. Specific antibody responses in heifers were tested by indirect enzyme linked immunosorbent assay (iELISA). The cellular immune response in dams was assessed by quantifying IFN-γ production and the percentages of T-cells (CD4+, CD8+ and γδ+) and monocytes in peripheral blood mononuclear cells (PBMC). Fetal fluids and tissue samples were tested using the indirect fluorescence antibody test, western blot, histopathology, immunohistochemistry and nested-PCR. A significant increase in N. caninum antibody response was detected in heifers of groups A and B from week 3 after inoculation (P<0.001). IFN-γ production was similar in groups A and B at week 13 (P>0.05). All fetuses were viable at necropsy. Specific IgG against N. caninum was detected in 1/4 fetal fluids recovered from groups A, C and D heifers and 3/4 fetal fluids from group B. Transplacental transmission could be determined in one fetus from group A and three fetuses from group B by nPCR. All fetuses from groups C and D were positive by nPCR. It is noteworthy that dams with higher CD4+/CD8+ ratios in PBMC, regardless of the experimental group, had lower pathology scores. The results of this study confirm that inoculation with live parasites pre-mating may provide at least partial protection against vertical transmission of N. caninum following challenge in heifers at early gestation.